Human Plasma Transcriptome Implicates Dysregulated S100A12 Expression: A Strong, Early-Stage Prognostic Factor in ST-Segment Elevated Myocardial Infarction: Bioinformatics Analysis and Experimental Verification - Zhai, Hu; Huang, Lei; Gong, Yijie; Liu, Yingwu; Wang, Yu; Liu, Bojiang; Li, Xiandong; Peng, Chunyan; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
The ability of this approach to identify dysregulated pathways and outcome-related genes following myocardial infarction remains unknown. Two gene expression datasets(GES60993 and GSE61144) were downloaded from GEO Datasets to identify altered plasma transcriptomes in patients with ST-segment elevated myocardial infarction(STEMI) undergoing primary percutaneous coronary intervention. GEO2R, GO/KEGG annotations, protein-protein interaction analysis, etc. were adopted to determine functional roles and regulatory networks of differentially expressed genes(DEGs). Dysregulated expressomes were verified at transcriptional and translational levels by analyzing the GSE49925 dataset and our own samples respectively. A total of 91 DEGs were identified in the discovery phase, consisting of 15 downregulated genes and 76 upregulated genes. Two hub modules consisting of 12 hub genes were identified. In the verification phase, six of the 12 hub genes exhibited the same variation patterns at the transcriptional level in GSE49925 dataset. Among them, S100A12 was showed the best discriminative performance for predicting in-hospital mortality and to be the only independent predictor of death during follow-up. Validation of 223 samples from our center showed that S100A12 protein level in plasma was significantly lower among patients who survived to discharge, but it was not an independent predictor of survival to discharge or recurrent major adverse cardiovascular events after discharge. The dysregulated expression of plasma S100A12 at transcriptional level is a robust early prognostic factor in STEMI patients, while the discrimination power of the protein level in plasma needs to be further verified by large-scale, prospective, international multi-center studies.